ASSESSMENT OF RESTAURANTS AND OTHER FOOD SERVICE SECTOR: TRENDS AND ANALYSIS IN ROMANIA - Viorela Gabriela CIOBOTEA (PETRESCU); Elena TOMA (DIACONU) (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The document focuses on the transformation and dynamics of the restaurant and food service market in Romania ranging from 2015 to 2022 with a special attention to the 2023 financial information. The research is based upon on particular information obtained from the National Statistics Institute and certain other financial related data bases in order to single out and address the major trends occurring in the sector. Analysis focuses on the economic variations, shifts in the consumption patterns of people, as well as the consequential effects on revenue and operational expenditures in the food service business. Furthermore, the analysis presents with national and regional dimensions of the sector development, the spatial imbalances, and the main determinants of the growth and the viability of the companies in this industry. The obtained results give important insights into the functioning of the restaurant and food service market place and explain in details the general state of the industry in the mentioned economic situation.